The Use of Pictures in Teaching Fiction Creative Writing among EFL Students - Ignasia Yuyun; Lidia Lestari Sibuea (University of Muhammadiyah Prof. DR. HAMKA, 2020)
This study investigated the use of pictures to facilitate English for Foreign Language (EFL) students in fiction creative writing. This study was conducted in a private university located in Jakarta. This study involved 5 junior students of the English Department. The students were expected to write fiction creative writing by using pictures. They had to describe the setting and the character in the pictures and developed them. In this study, the students had one meeting to write a fiction writing without using the picture and four meetings using the picture. The result of this study reveals that the use of the pictures to facilitate EFL students in fiction creative writing is useful to facilitate them to get the ideas, raise their motivation, and build their imagination in doing fiction creative writing